Europe-Afrique : des acteurs en quête de scénarios - Bach, Daniel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
With the marginalization of Africa in international trade, previous models for operationalizing relations with Europe have become obsolete. There is increasingly a trend towards uncoupling between North Africa, the Republic of South Africa, and Black Africa. North Africa has broken away to the point of regarding itself as a hinterland of Europe. South Africa is likely to become both a crossroads and a transit point in trade between Europe, Africa, and the Pacific region. In Black Africa, the only current scenarios for reconnection with the rest of the world seem to amount to pointing out this subregion's capability to do harm if it were ever abandoned.